ANALISIS PENGARUH ASPEK MAKROEKONOMI TERHADAP TINGKAT PROFITABILITAS BANK UMUM DI INDONESIA - Suci Wulandari (2023)
This research was conducted to determine the effect of imports, money supply, GDP, and oil prices on profitability. This research uses twenty-one sample banks in Indonesia that are included in the KBMI list according to OJK and BI. The total data used in the study were 504 data from 2016 - 2021 on a quarterly basis using a purposive sampling technique to select the sample to be researched. The data used is sourced from Bank Indonesia and the financial statements of each bank. Panel data analysis is a hypothesis testing technique in this study by utilizing the Stata 17 program and an alpha level of 5%. The partial results showed that imports, money supply, and GDP had an effect on profitability, while world oil prices had no effect on profitability. The results also show that simultaneously the four independent variables affect the profitability.